Femicidio e investigación policial. El enfoque de género como imperativo para evitar la impunidad. Análisis del año 2015 - Reyes Reinoso, Janice Cristina (2018)
The criminal investigation of femicide has regained importance and relevance in recent years, more because of the legal characterization of this crime. In Ecuador, DINASED is created as a unit destined to the investigation of this crime and of others that imply an injury to the good of life. However, in these investigations it is necessary to consider gender perspectives in order that there is no impunity, bad typification of the legal figure and the consequent loss of data in the general statistics of homicides. The present work focuses on the analysis of the performance of the police investigative level that leads to the typification of femicide contrasted with international research protocols that serve as a model. With this, it is intended to show that the mere definition of crime is not enough, because elements of conviction based on gender are needed to be able to sanction it in a legal manner